The Need for Open Data on Air Quality Monitoring in Logistically Difficult Environments - Hodoli, C.G.; Abubakari, A.; Adzaho, G. (Clean Air Journal, 2018)
The article provides commentary on the challenges of accessing open air quality in Ghana, and steps that can be taken to increase public knowledge, and implement relevant policies and actions to ensure clean air is available to all.